Editorial to the Special Issue “Gulliver in the Country of Lilliput: An Interplay of Noncovalent Interactions (Volume II)” - Ilya G. Shenderovich (Molecules, 2025)
Noncovalent interactions are the bridge between the ideal gas abstraction and the real world [...]